Development of a business framework to integrate informal SMMEs and entrepreneurs with the formal South African economy - Brand, Riaan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2006.